Evaluation of the Antimicrobial Activity of Caesalpinia pulcherrima (L) Swartz Extract against Microbes that Cause Dental and Oral Infections and Determination of the Total Flavonoid and Total Phenolic Contents of the Plant: Antimicrobial activity against bacteria that cause dental and oral infections of Caesalpinia pulcherrima (L) Swartz - Lolo Lukitaa, Bertha; Elya, Berna; Bagio Budiardjo, Sarworini (Iranian Journal of Pharmaceutical Sciences, 2019)
In Indonesia, Caesalpinia pulcherrima (L) Swartz is widely grown as an ornamental, whereas it is used as a medicinal herb in Mexico as an alternative treatment for dental and oral infections. At present, only fruit and root parts of the plant are used. The aim of this study was is evaluate the anti-microbial activity of ethanol extract of fruit, leaves, flowers and stems against microbes that cause dental and oral infections and determination of the total flavonoid and total phenolic contents of C. pulcherrima (L) Swartz. Porphyromonas gingivalis, Sterptococcus mutans, Enterococcus faecalis and Candida albicans are microbes that cause dental and oral infections. All parts of the plant were extracted by maceration using 70% ethanol for 24 hours at 150-300C, and extracts were concentrated using a reflux method and dried over a water bath. The total flavonoid contents were determined using the aluminium chloride colorimetric assay at 415 nm. The total phenolic content was determined using Folin–Ciocalteu reagent in a 1:4 ratio at a wavelength of 750 nm using a microplate reader. Antimicrobial activity was determined by the diffusion method. The total flavonoid content was expressed as milligram quercetin equivalent (QE) per gram of plant extract. The highest total flavonoid content per gram of plant extract was found in the flowers (10.06 ± 0.08 mg QE/g), and the lowest total content was found in the leaves (0.34 ± 0.02 mg QE/g). The highest phenolic content was also found in the flowers (498.52 ± 1.96 mg gallic acid equivalent [GAE]/g), and the lowest total phenolic content was detected in the leaves (216.76 ± 1.00 mg GAE/g). A 100% crude ethanol extract of the flower and fruit parts exhibited antimicrobial activity against bacteria P. gingivalis, S. mutans, E. faecalis and C. albicans) that cause dental and oral infections. A 2% crude flower extract showed the highest antimicrobial activity against P. gingivalis (14.49 ± 0.465 mm), S. mutans (9.02 ± 0.607 mm), E. faecalis (9.67 ± 0.297 mm) and C. albicans (19.44 ± 0.207 mm). The ethanol extract of the flowers had the highest contents of total flavonoids and total phenols and the most antimicrobial activity against the studied compared to the other parts. This results of the present study revealed valuable information and also support the continued sustainable use of C. pulcherrima (L) Swartz in a traditional system of medicine.